PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN TRANSAKSIONAL TERHADAP KEPUASAN KERJA DAN KINERJA KARYAWAN DI PT. TOHITINDO MULTI CRAFT INDUSTRIES KRIAN - SETIAWAN, DENNY (Universitas Katolik Widya Mandala Surabaya, 2013)
A leader must be able to influence his subordinates to carry out tasks that were ordered without coercion so that subordinates voluntarily will behave and perform according to the demands of the Organization through its directives. A leader must be able to influence his subordinates to carry out tasks that were ordered without coercion so that subordinates voluntarily will behave and perform according to the demands of the Organization through its directives. Transformational and Transactional leadership is developed based on Maslow's opinion about the levels of human needs. In a variety of Transformational and Transactional leadership study found to have close links with job satisfaction, which in turn will improve employees performance themselves. In this study used is the conclusive research on the study of experimental or causal research. Retrieval technique of sampling used is non probability sampling. The type of method used is the purposive sampling. The sample used was 150 employees of PT Multi Tohitindo Craft. Data were collected using a questionnaire. The technique used is the analysis of structural equation models with the help of Amos programs.